Hubungan Usia Dan Paritas Dengan Kejadian Anemia Pada Ibu Hamil Di PMB Bidan Daini Zulmi, S.S.T., M.Tr. Keb Tahun 2022 - Aminah; Hullyatun Nufus; Sulis (Prodi DIII Kebidanan La Tansa Mashiro, 2023)
Pregnancy Anemia is generally associated with physiological changes that occur in pregnancy. The expansion of plasma volume is closely related to the relative decrease in hemoglobin concentration in addition to fetal growth that requires iron and folate, making pregnant women vulnerable or at high risk of deficiency. The aim is to determine the relationship between age and Anemia in pregnant women at PMB Bidan Daini. The prevalence of Anemia in Banten Province was 37.1% based on Banten provincial data. The type of analytical obsevational research using case control design. the number of samples in this study were 62 pregnant women from 70 populations and a fixed sample of 70 pregnant women was taken. Sampling using total sampling technique according to inclusion criteria, analyzed using Univariate Analysis and Bivariate Analysis with Chi Square statistical test. The results of the study in each variable p value <0.05. The conclusion is that there is a relationship between age and the incidence of Anemia in pregnant women where pregnant women at PMB Bidan Daini. Suggestions to prospective or pregnant women should plan pregnancy at reproductive age, namely 20 years to 35 years and mothers should know the nutritional needs during pregnancy planning and pregnancy to achieve a healthy pregnancy and minimal risk of complications.